Natural glycolipids as a surface treatment prevent fungal spoilage of fermented sausages during ripening - Panagiotis Chanos; Thorben Sieksmeyer; Jessica Block-Ahrens; Dirk Steinriede; Christian Hertel (Food Control, 2026)

Novel concept to guide systolic heart failure medication by repeated biomarker testing—results from TIME-CHF in context of predictive, preventive, and personalized medicine - Nasser Davarzani; Sandra Sanders-van Wijk; Micha T. Maeder; Peter Rickenbacher; Evgueni Smirnov; Joël Karel; Thomas Suter; Rudolf A. de Boer; Dirk Block; Vinzent Rolny; Christian Zaugg; Matthias E. Pfisterer; et al. (EPMA Journal, 2018)

The interplay of adult and larval time constraints shapes species differences in larval life history - Dirk J. Mikolajewski; Marjan De Block; Robby Stoks (Ecology, 2015)
In animals with a complex life cycle, larval life‐history plasticity is likely shaped by the interplay of selective factors in both larval and adult stages. A wide interspecific variation in responses to larval time constraints imposed by seasonality has been documented. Few studies have addressed differences among closely related species in the evolutionary trajectories of age and size at metamorphosis and their link with larval growth rate under time constraints. None have considered how species‐specific length of the reproductive season affects larval developmental responses to time constraints. We tested in four Coenagrion damselfly species whether species with a longer reproductive season, facing a smaller threat of missing out on reproduction, react less to larval time constraints and pre‐winter food shortage by accelerating development rate and growth rate, and therefore pay less physiological costs. All species increased development and growth rates under larval time constraints. The magnitude of this increase negatively correlated across species with the length of the reproductive season. Under larval time constraints, only the species exhibiting the longest reproductive season suffered a delayed emergence and a reduced investment in energy storage, yet also showed an increased immune function. Under a longer reproductive season, evolution may favor compensation for larval constraints after metamorphosis. Growth rate was accelerated after pre‐winter food shortage to the same extent across species; effects on age and mass at emergence also did not differ among species. Time constraints associated with the length of the reproductive season may predictably contribute to species differences in their response to time constraints imposed in the larval stage. Our study adds empirical proof that the interplay of selective factors in the larval and adult stages may determine life‐history plasticity with regard to larval time constraints.

Transforming petals into sepaloid organs in Arabidopsis and oilseed rape: implementation of the hairpin RNA-mediated gene silencing technology in an organ-specific manner - Marina Byzova; Christoph Verduyn; Dirk De Brouwer; Marc De Block (Planta, 2004)